Community Engagement and Patient-Centered Implementation of Patient-Reported Outcome Measures (PROMs) in Gender Affirming Surgery: a Systematic Review - Clennon, Emily K.; Martin, Leigh H.; Fadich, Sarah K.; Zeigen, Laura; Blasdel, Gaines; Sineath, Craig; Dy, Geolani W. (Current sexual health reports, 2022)
Purpose of review Analyze the utilization of patient-centered outcomes research (PCOR) methods in the literature containing patient-reported outcome measures (PROMs) for gender affirming surgery (GAS). Recent findings Multiple recent systematic reviews have demonstrated that the majority of PROMs used to assess GAS are either ad hoc measures never intended for validation or are neither specific to nor validated for the population or intervention being studied. This review builds on prior works with inclusion of articles related to facial and vocal GAS and presentation of PCOR recommendations and best practices based on review findings. Summary A systematic review of records in PubMed and Scopus using search terms related to GAS and PROMs yielded 652 total articles of which 158 were included in the final analysis. Just over half of included articles utilized validated PROMs, though only 38% of those articles utilized a PROM that had been validated in the TGNB population. Thirteen (8.2%) studies detailed the involvement of patients in PROM development as subjects, and only 4 (2.5%) utilized PCOR methods that engaged TGNB individuals as research stakeholders. Utilization of PCOR methods in research evaluating outcomes of GAS is exceedingly rare despite increasing use of PROMs over time. To collect data that are both accurate and meaningful to the TGNB population, PCOR methods must be adopted within this field.